Differential persuasive effects of high and low credibility sources on Singapore and China individual investors' judgement. - Nguyen, Ha Linh. (2008)
With the proliferation of investment information, investors are likely to have repeated exposure to similar information from sources with varying credibility. Contrary to main effects studies, psychology research has found that low credibility source may interact with other factors to be more persuasive than high credibility source. Our experimental results, using Singapore accountancy undergraduates as participants, indicate that for individual investor holding an initial negative position, negative news from a low credibility source is more persuasive than a high credibility source. Furthermore, repeating similar negative news from another low credibility source enhances the overall persuasiveness of the news regardless of whether the first exposure to the news is from a high or low credibility source, although the effect is stronger for the former. With repeated exposure from a high credibility source, we obtained weak support on the decrease in overall persuasiveness when the initial source credibility is low and opposite result when the initial source credibility is high. All the above results were obtained (except that the effects were stronger) when we replicated the experiment conditions using China participants.